Determinação da atividade antioxidante de amostras de chás e fontes comerciais de vitamina C, utilizando um biossensor enzimático - RIBEIRO, Danilo Braga (2020)
Free radicals are chemical species that show high reactivity because they have an unpaired valence electron in their structure and, consequently, a generally very short half-life, being considered potent oxidizing agents. Antioxidants are synthetic or natural compounds capable of preventing or delaying oxidative damage caused by these chemical species. In the present work, an amperometric biosensor was used to determine the antioxidant activity of teas and drugs available on the market. The determination of the antioxidant potential was based on the online monitoring of hydrogen peroxide formed during the oxidation reaction of hypoxanthine to uric acid, catalyzed by the enzyme xanthine oxidase (XOD). A three electrodes-based sensor was used, and the performance of the following electrochemical mediators was evaluated: meldola blue combined with Reineck's salt (MBRS), Prussian blue (PB) and cobalt phthalocyanine (CoPC). Other operational conditions, such as the polymerization time in the enzymatic immobilization procedure and the agitation process during the chronoamperometric measurements, were analyzed. The PB mediator showed to be the most efficient and the photopolimerization in PVA-AWP was the most suitable immobilization process. After optimizing the biosensor, as well as the operational parameters, it proved to be stable for a period of 7 months, with detection and quantification limits of 4.93 µmol.L-1 and 16.43 µmol.L-1 , respectively. The system was then used to determine the antioxidant capacity of commercial teas and effervescent vitamin C from different suppliers, with sample preparation procedures previously defined. Chamomile and mint teas shoed to have about 67% and 64% of antioxidant potential, respectively. Tests with Vitamin C tablets showed that the formulations may have different antioxidant capacities, varying from 26 to 37%, although their labels indicate the same vitamin C content.